Uncertainties in energy markets and their consideration in energy storage evaluation - Keles, Dogan (Produktion und Energie / Karlsruher Institut für Technologie, Institut für Industriebetriebslehre und industrielle Produktion u. Deutsch-Französisches Institut für Umweltforschung, 2013)
This book successfully illustrates the modeling of electricity prices with the help of stochastic processes. The relatively new phenomenon of negative prices is also integrated into the models. The integration of feed-in from wind power plants in energy models is also very innovative. This approach helps to simulate electricity prices in order to take into account the ""merit-order effect of renewable energy"". Finally, the models are used for the techno-economic evaluation of energy storages.